AN EVALUATION ON İSMAİL DEDE EFENDİ AND HOCA ZEK?İ DEDE - Demi?Rtaş, Yavuz (Ankara Haci Bayram Veli University, 2022)
İsmail Dede and Zek?i Dede are two great musicians who have contributed to the enrichment of the Classical Turkish Music Repertoire with their many works in many genres. They have been at the forefront of the main sources from which this repertoire has survived to the present day. Although there are many people with the title of “Dede” in Classical Turkish Music, the only person known as “Dede Efendi” is İsmail Dede who left his mark on the first half of the 19th century; Zek?i Dede, on the other hand, left his mark on the second half of the century as one of the few people known as “Hodja” (Hoca). In addition to their current talents, the musical understanding of the Mawlaw? sect, to which they are deeply attached, played an important role in the success of both Dedes in the art of music. İsmail Dede and Zek?i Dede’s existence in the 19th century, was the occasion for the Ottoman Empire, which was on the verge of collapse in almost every respect, to achieve a magnificent victory in the field of music in this century. Our study includes information on the lives, mystical aspects and musicianships of İsmail Dede and Zek?i Dede, who made great contributions to the development and spread of Turkish Music with the works they composed, the students they trained, the classical repertoire they conveyed together with their styles and their evaluations. © 2022 Ankara Haci Bayram Veli University. All rights reserved.
İSMAİL DEDE EFENDİ VE HOCA ZEKAİ DEDE ÜZERİNE BİR DEĞERLENDİRME
Keywords: Composer; Musician; Turkish Music; Zek?i Dede; İsmail Dede